Transfer of heavy metals through terrestrial food webs: a review - Gall, Jillian E.; Boyd, Robert S.; Rajakaruna, Nishanta (Environmental monitoring and assessment, 2015)
Heavy metals are released into the environment by both anthropogenic and natural sources. Highly reactive and often toxic at low concentrations, they may enter soils and groundwater, bioaccumulate in food webs, and adversely affect biota. Heavy metals also may remain in the environment for years, posing long-term risks to life well after point sources of heavy metal pollution have been removed. In this review, we compile studies of the community-level effects of heavy metal pollution, including heavy metal transfer from soils to plants, microbes, invertebrates, and to both small and large mammals (including humans). Many factors contribute to heavy metal accumulation in animals including behavior, physiology, and diet. Biotic effects of heavy metals are often quite different for essential and non-essential heavy metals, and vary depending on the specific metal involved. They also differ for adapted organisms, including metallophyte plants and heavy metal-tolerant insects, which occur in naturally high-metal habitats (such as serpentine soils) and have adaptations that allow them to tolerate exposure to relatively high concentrations of some heavy metals. Some metallophyte plants are hyperaccumulators of certain heavy metals and new technologies using them to clean metal-contaminated soil (phytoextraction) may offer economically attractive solutions to some metal pollution challenges. These new technologies provide incentive to catalog and protect the unique biodiversity of habitats that have naturally high levels of heavy metals.